Review and evaluation of hydrogen production options for better environment - Acar, Canan; Dincer, Ibrahim (ELSEVIER SCI LTD, 2019)
In this study, different hydrogen production sources and systems and some hydrogen storage options are comparatively investigated in detail. Economic, environmental, social, and technical performance and reliability of the selected options are compared in detail. Biomass, geothermal, hydro, nuclear, solar, and wind are the selected hydrogen production sources; biological, thermal, photonic, and electrical are the selected hydrogen production methods; and chemical hydrides, compressed gas, cryogenic liquid, metal hydrides, and nanomaterials are the selected hydrogen storage systems. In addition, some case studies and basic research needs to enhance the performance of hydrogen energy systems and to tackle the major challenges of the hydrogen economy are provided. The results show that solar has the highest environmental performance (8/10) and the total average ranking (7.40/10), nuclear has the lowest environmental performance (3/10), and geothermal has the lowest total average ranking (4/10/10) among selected hydrogen production sources. Hydrogen production systems' comparison indicates that photonic options have the highest environmental performance ranking (8/10), thermal options have the lowest environmental performance ranking (5/10), electrical options have the highest average ranking (7.60/10), and biological options have the lowest average ranking (4.80/10). (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Hydrogen economy; Sustainability; Energy; Sources; ENERGY DEMAND; SOLAR HYDROGEN; TECHNOECONOMIC ANALYSIS; TRANSPORTATION FUEL; ROAD TRANSPORTATION; RENEWABLE HYDROGEN; STORAGE MATERIALS; NATURAL-GAS; SYSTEM; CARBON; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology